Around the admissibility of the transcription of the birth certificate of a child of same-sex parents - Rokicka-Murszewska, Karolina; Wojciechowski, Kamil (Studia Iuridica Toruniensia, 2023)
The refusal to perform the obligatory transcription of a birth certificate, required by the Polish legislator, effectively blocked the way for Polish citizens to apply for Polish identity documents. Discrepancies in the jurisprudence of administrative courts and shortcomings in legislation limit the fundamental rights of children with same-sex parents. The authors also examine whether the case law of the Court of Justice of the European Union offers an opportunity for change.